Reproductive performance of snakehead fish (Channa striata) induced by oodev hormone - Delia, Rievika Nur; Nuraini, Nuraini; Aryani, Netti; Heltonika, Benny (Acta Aquatica: Aquatic Sciences Journal, 2023)
Snakehead fish is a fish that has a high level of consumption and has many benefits in the health sector, but cultivation activities have not been carried out intensively because of the availability of snakehead fish which still utilizes catches from nature. In cultivation activities, the use of hormones is commonly used, one of which is used to support reproductive performance. One of them is the Oodev hormone, so this study aimed to determine the effect of Oodev with different doses on the final gonad maturation of snakehead fish. The research method used was a completely randomized design experiment with four treatments and three replications. The treatments were P0 (Oodev 0 mL/kg), P1 (Oodev 0.5 mL/kg), P2 (Oodev 1 mL/kg), P3 (Oodev 1.5 mL/kg). Oodev injections were carried out on TKG II fish at an interval of every 7 days. During maintenance, the fish were fed golden snails and small fish 2 times a day. The result of the research showed that Oodev is significant in the gonad maturation of common snakehead. The treatment P3 injection dose of 1.5 mL/kg with maturation gonad time for 16 days, ovi somatic index 4.26%, egg diameter increases of 0.113 mm, fertilization rate 91.43%, hatching rate 90.96. It was concluded that the Oodev injection had a significant effect on the gonad maturity of snakehead fish (P<0.05) in the P3 treatment (Oodev 1.5 mL/kg).Keywords: Channa striata; Dose; Gonad maturation; Hormone; Oodev